2018
DOI: 10.1590/1413-81232018233.12532016
|View full text |Cite
|
Sign up to set email alerts
|

Evolução e associação do IMC entre variáveis sociodemográficas e de condições de vida em idosos do Brasil: 2002/03-2008/09

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
2
5
0
10
Order By: Relevance
“…In the anthropometric evaluation, the majority of the elderly did not present a risk in relation to the nutritional status. This is consistent with the results of a recent study, which evidenced an increase in the prevalence of overweight and obesity and a decrease in underweight among elderly Brazilians 60 or older, of both genders, in the period from 2002/3 to 2008/9, reinforcing the occurrence of the nutritional transition in Brazil [22]. Nutritional status and gender also had no significant association in the detection of basic tastes, a fact that corroborates with Neumann's study.…”
Section: Discussionsupporting
confidence: 92%
“…In the anthropometric evaluation, the majority of the elderly did not present a risk in relation to the nutritional status. This is consistent with the results of a recent study, which evidenced an increase in the prevalence of overweight and obesity and a decrease in underweight among elderly Brazilians 60 or older, of both genders, in the period from 2002/3 to 2008/9, reinforcing the occurrence of the nutritional transition in Brazil [22]. Nutritional status and gender also had no significant association in the detection of basic tastes, a fact that corroborates with Neumann's study.…”
Section: Discussionsupporting
confidence: 92%
“…Health conditions and weight change among the elderly contributed to the increase in weight and obesity 5,14 found in the second wave, contrasting studies that demonstrate weight reduction among elderly people 15,16 and the results found in the first wave of the study. Reductions in mobility and prevalence of comorbidities generally associated with weight gain 17 , such as cardiovascular diseases, as well as stigmatizing factors of obesity, can favor individuals having a negative perception of their own health.…”
Section: Supplement 1 -Flowchart Of Total Population and Losses Durinmentioning
confidence: 59%
“…4 Data from the Family Budgets Survey reveal, for example, that between 2002/2003 and 2008/2009 prevalence of excess weight (overweight and obesity) increased from 45.1% to 53.9% among people 60 to 74 years old and from 32.5% to 43.6% among those aged 75 or over. 5 International studies indicate greater frailty and mortality among elderly people whose body weight changed. 6,7 Little is known, however, about the health profile of elderly people living in developing countries whose body weight has changed.…”
Section: International Studies Indicate Greater Frailty and Mortalitymentioning
confidence: 99%
“…A taxa de mortalidade por esta doença no Brasil é de cerca de 183,3 pessoas a cada 100.000 habitantes sendo uma das maiores no mundo, perdendo apenas para China e o leste europeu(JUNIOR, 2020).No ano de 2014, o Brasil registrou 87,234 mil (7,1%) óbitos pelo infarto agudo do miocárdio. O Amazonas ocupa o segundo lugar entre os estados na região Norte de mortalidade entre homens e mulheres, ficando apenas atrás do Paraná, apesar disso a média proporcional estadual é de apenas 4,7% e quando passada para a média nacional é de 0,8% representando a menor de todo o Brasil no ano de 2014(SILVA et al, 2018).O número de mortalidade no ano de 2017, no Brasil, de acordo pela raça é de 7,3% para pessoas brancas, 7,1% para amarelas, 6,9% para pessoas negras e indígenas de 5,3% respectivamente(BRASIL, 2019).No Brasil, temos o programa de prevenção e controle de hipertensão e diabetes (HIPERDIA), estes que são fatores de risco para o desenvolvimento do infarto agudo do miocárdio, o programa visa à redução de morbimortalidade por doenças cardiovasculares dentre elas está o IAM, porém, mesmo com a implementação deste programa os números de mortalidade permanecem os mesmos(SANTOS et al, 2018).Segundo estudos científicos, os sintomas do infarto agudo do miocárdio geralmente ocorrem pela parte da manhã. Os óbitos ocorrem por vezes fora de o ambiente hospitalar, por tanto, sem assistência medica, sendo considerados 54 a 60% na primeira hora do dia e alcançando 80% nas primeiras 24 horas após o início dos sintomas.…”
unclassified